2015
DOI: 10.3109/09546634.2015.1067669
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sodium hypochlorite (bleach) baths to reduceStaphylococcus aureuscolonization in childhood onset moderate-to-severe eczema: A randomized, placebo-controlled cross-over trial

Abstract: This study demonstrated that a four-week, twice-weekly regime of diluted bleach baths is not more useful than water baths in reducing S. aureus colonization/infection and improving AD. A longer treatment period is needed to evaluate if the short treatment duration was the main cause for the discrepancy in outcome from other bleach-bath trials. The usage of a portable bath tub obviates the problems associated with unavailability of bathing facilities in some families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 27 publications
0
61
1
2
Order By: Relevance
“…A study showed that children bathing in 0.005% bleach experienced an improvement of their AE . In a recent study, sodium hypochlorite baths did not show superiority to water baths concerning the severity of AE, but allowed a reduction in topical corticosteroid and antibiotic usage . Salt baths may be beneficial because of removing the dead keratin material .…”
Section: Basic Therapy Of Disturbed Skin Barrier Function and Emolliementioning
confidence: 99%
“…A study showed that children bathing in 0.005% bleach experienced an improvement of their AE . In a recent study, sodium hypochlorite baths did not show superiority to water baths concerning the severity of AE, but allowed a reduction in topical corticosteroid and antibiotic usage . Salt baths may be beneficial because of removing the dead keratin material .…”
Section: Basic Therapy Of Disturbed Skin Barrier Function and Emolliementioning
confidence: 99%
“…The Cochrane Review has discussed the different approaches for the eradication of S. aureus as a treatment for AD. The results showed that improvement of disease was observed only with the use of bleach bath therapy . The American Academy of Dermatology announced in 2014 that bleach bath therapy should be recommended as a treatment option for patients with moderate to severe AD and possible presence of infection .…”
Section: Cq24 Is Bleach Bath Therapy Recommended For the Treatment Omentioning
confidence: 99%
“…Antimikrobiyal ajanlar sadece klinik olarak enfeksiyon bulgularının olduğu olgulara saklanmalıdır. Son zamanlarda dilüe edilmiş çamaşır suyu banyoları S. aureus kolonizasyonuna ve enfeksiyonuna yönelik uygulanan popüler bir yöntemdir 98,99 . Bu yöntemde yarım bardak (120 mL) evde kullanılan %6'lık çamaşır suyu tam doldurulmuş (150 litre) küvet içinde %0,005 konsantrasyonda olacak şekilde dilüe edilir.…”
Section: Topikal Antimikrobiyaller Antiseptiklerunclassified
“…Çamaşır suyu banyosuyla beraber intranazal olarak uygulanan mupirosin kremin antienflamatuvar bir ajan ve nemlendiriciyle birlikte kullanılmasının özellikle stafilokokkal deri enfeksiyonlarının sık görüldüğü hastalarda iyi bir tedavi rejimi olduğu bildirilmektedir 100 . Yapılan bir çalışmada ise çamaşır suyu banyosunun ne kolonizasyon üzerine ne de AD kliniği üzerine sadece su ile yapılan banyodan bir üstünlüğü olmadığı gösterilmiştir 98 . Bu nedenle etkili olduğunu söyleyebilmek için daha fazla bilimsel veriye ihtiyaç vardır.…”
Section: Topikal Antimikrobiyaller Antiseptiklerunclassified